"For the Public Benefit" Railways in the British Cape Colony - Alfonso Herranz-Loncán; Johan Fourie (African Economic History Network (AEHN), 2016)
Built mostly to support the early mining industry, the Cape Colony's railways reduced the cost of transport to the interior and increased labor productivity in the Colony from 1859 to 1905 by, we calculate, 30 percent. Little of the gains went to the state-owned company: the Cape parliament seems always to have seen the railways as a means to development. But the politically overrepresented western parts of the Colony gained much more than underrepresented areas like Basutoland or the Transkei. While boosting the economy, the railways also had distributional effects, with consequences for racial segregation in twentieth-century South Africa.
Keywords: H40; N40; O10; 330; railways; infrastructure; public goods; South Africa; social savings